Internalization of Sufi Moral Values in Contemporary Islamic Education Practices - Subhan Fadli; Lukman Hakim; Evi Laily Musalimah (MASI Mandiri Edukasi, 2026)
This study stems from the problems of moral crisis and academic ethical degradation in contemporary Islamic education, indicating that the integration of spiritual dimensions into the learning process is not yet optimal. Therefore, this study aims to analyze the process of internalizing Sufi moral values in Islamic education practices and identify their impact on character building among students. The research uses a qualitative approach, employing field research methods such as direct observation, in-depth interviews, and the analysis of documentation from lecturers and students, who serve as the main informants. The results show that the internalization of Sufi moral values occurs through three main mechanisms: integrating values into the curriculum and learning, consistent spiritual habits, and strengthening communication ethics in academic interactions. Values such as sincerity, patience, humility, and muraqabah (self-reflection) have been proven to shape polite attitudes, improve emotional control, and strengthen students’ academic integrity. These findings confirm that the internalization of Sufi moral values contributes to the development of a dialogical, reflective, and character-oriented Islamic educational culture.